2018
DOI: 10.1016/j.ijpharm.2017.11.070
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of PEGylated liposomes incorporating lipophilic lomeguatrib derivatives for the sensitization of chemo-resistant gliomas

Abstract: Liposomal delivery is a well-established approach to increase the therapeutic index of drugs, mainly in the field of cancer chemotherapy. Here, we report the preparation and characterization of a new liposomal formulation of a derivative of lomeguatrib, a potent O-methylguanine-DNA methyltransferase (MGMT) inactivator. The drug had been tested in clinical trials to revert chemoresistance, but was associated with a low therapeutic index. A series of lomeguatrib conjugates with distinct alkyl chain lengths - i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…10 The notion that polymersome membranes are much tougher than liposomal ones was first put forward by Discher et al who showed that poly(ethyl ethylene) (PEE) 37 -b-poly(ethylene oxide) 40 (PEO, also referred to as poly(ethylene glycol), PEG) polymersomes resisted higher areal strains than liposomes made of the unsaturated phospholipid 1-stearoyl-2-oleoyl-sn-glycero-3-phosphatidylcholine (SOPC, phase transition temperature T m B 6 1C) in micropipette aspiration experiments. 11 A subsequent study by the same group demonstrated that poly(butadiene) 46 (PBD)-b-PEO 26 , PBD 55 -b-PEO 50 , PBD 125 -b-PEO 80 , and PBD 250 -b-PEO 150 polymersomes ruptured at an areal expansion of B10-40%, while SOPC liposomes ruptured at B4%. 5 This study is the origin of the widely propagated notion that polymersomes are considerably more stable than liposomes.…”
Section: Jean-christophe Lerouxmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The notion that polymersome membranes are much tougher than liposomal ones was first put forward by Discher et al who showed that poly(ethyl ethylene) (PEE) 37 -b-poly(ethylene oxide) 40 (PEO, also referred to as poly(ethylene glycol), PEG) polymersomes resisted higher areal strains than liposomes made of the unsaturated phospholipid 1-stearoyl-2-oleoyl-sn-glycero-3-phosphatidylcholine (SOPC, phase transition temperature T m B 6 1C) in micropipette aspiration experiments. 11 A subsequent study by the same group demonstrated that poly(butadiene) 46 (PBD)-b-PEO 26 , PBD 55 -b-PEO 50 , PBD 125 -b-PEO 80 , and PBD 250 -b-PEO 150 polymersomes ruptured at an areal expansion of B10-40%, while SOPC liposomes ruptured at B4%. 5 This study is the origin of the widely propagated notion that polymersomes are considerably more stable than liposomes.…”
Section: Jean-christophe Lerouxmentioning
confidence: 99%
“…Conjugating small and large molecules to the polymersomeforming block copolymer can be used to encapsulate drugs and decorate polymersomes with targeting ligands. [77][78][79] Incorporating drugs using a biodegradable linker (analogously to drug-lipid conjugation for liposomes 80,81 ) may provide prolonged release kinetics due to an improved retention in the vesicle. 82 To increase the permeability of polymersomes for hydrophilic molecules and ions in a selective manner, transmembrane channel proteins can be incorporated into the membrane.…”
Section: Hydrophilic Drugs and Membrane Proteinsmentioning
confidence: 99%
“…Exchange rates are usually studied by incubating the L-LDCs with whole blood, plasma or serum [18], and, although these in vitro tests might not accurately reflect the in vivo performance of the L-LDCs, they provide valuable preliminary insights. In the case of alkylated LDCs, it was found that the exchange rate to biological membranes was inversely related to the alkyl chain length [19,20].…”
Section: In Vitro Drug Release Of L-ldcsmentioning
confidence: 99%
“…We believe that the mechanism of release of our system relies on drug transfer between the particles, the macrophage lipid membranes, and eventually the lipid membranes of the neighboring cells. Furthermore, reports have indicated that LDC tail length plays a role in the release rate, with longer tails releasing more slowly . This point reinforces the idea that differences in conjugate efficacy in both carrier macrophages and tumor spheroids is likely due to control of conjugate transfer between lipid membranes.…”
Section: Resultsmentioning
confidence: 99%